Landasan Implementasi Ekonomi Syariah Dalam Perspektif Maqāṣid al-Sharī‘ah - Mugni Muhit; Mohamad Anton Athoillah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Islam as a doctrine will certainly be the main foundation in every human activity that has claimed and positioned Islam as its belief. It is with this doctrine that all activities are guarded and regulate all forms of human activity universally and comprehensively, between humans as creatures and God as Creator and humans as His fellow creatures. A Muslim who needs a means of living, of course, will not be able to avoid all kinds of activities related to the economy, therefore as Muslims in their economic activities they must be based on God's doctrine to achieve prosperity and benefit. For this reason, the purpose of this research is to examine in more detail the transcendent basis of Islamic economics from the perspective of Maqāṣid al-Shari'ah, so that in its implementation, the economic welfare of Muslims increases to become a benefit that has a positive impact on other benefits. Keywords: Foundation, Implementation, Islamic Economics, Maqāṣid Sharī'ah